Sliding-mode control for target tracking of omnidirectional mobile robots subject to impulsive deception attacks - Liu, Chang; Wei, Tengda; He, Xinyi; Li, Xiaodi (Chaos, solitons and fractals, 2024)
This article focuses on the target tracking of omnidirectional mobile robots (OMRs) subject to impulsive deception attacks. The impulsive deception attacks describe the cyber attacks causing instantaneous changes of system states at uncertain moments. To resist such kind of attacks, sliding-mode control (SMC) strategies are designed for the global asymptotic stability of the tracking errors of the OMRs. With the designed sliding-mode controller, the OMRs are capable of tracking the fixed and time-varying target in an experiment platform consisting of OMRs, wireless router and control center, which shows the robustness of the system with respect to impulsive deception attacks and the effectiveness of theoretical results.